The Role of the Pie-Crusting Technique of the Medial Collateral Ligament in the Arthroscopic Inside-out Technique for Medial Meniscal Repair With or Without Anterior Cruciate Ligament Reconstruction: A Satisfactory Repair Technique - Mehmet Erdem, M.D; Levent Bayam, M.R.C.S. (Ed); Ahmet Can Erdem, M.D; Deniz Gulabi, M.D; Abdulhalim Akar, M.D; Alauddin Kochai, M.D (Elsevier, 2021)
Purpose: To assess the results of a technique for pie crusting of the medial collateral ligament (MCL) and inside-out medial meniscal repair and perform a comparison with the literature. Methods: This retrospective study consisted of electronic data collection between 2012 and 2017 with a minimum of 2 years' follow-up. The inclusion criteria were the presence of difficult medial meniscal tears with joint tightness requiring pie crusting and the presence of acute or chronic tears of zone I or II with or without anterior cruciate ligament reconstruction (ACLR) using hamstring autograft during the same session. The primary outcome of the study was the achievement of good results with the aforementioned technique. There was no control group. All patients underwent assessments at 1, 2, and 6 months in outpatient clinics. At 6 months, the Lysholm knee score was calculated. For statistical analysis, the Social Science Statistics online program was used to perform descriptive analysis and assess any associations between the variables. Results: This study included 53 patients from a single surgeon's practice; of these patients, 31 underwent additional ACLR using hamstring autograft during the same session. The mean age was 29.43 years (range, 14-49 years), and the mean increase in the medial joint space width was 3.21 mm (range, 2-5 mm) with pie crusting. At 6 months, the average Lysholm score was 93 (range, 67-100) and the average visual analog scale score was 0.8 (range, 0-4). There was no meaningful association between age, tear pattern, chronicity of tear, joint space width obtained after pie crusting, and associated anterior cruciate ligament tear. Patients returned to their daily activity level at 4.5 months on average and returned to sporting activities at 7.4 months on average. Saphenous nerve symptoms were observed in 5 patients, but no infection or instability was documented in the follow-up period. Conclusions: In this study, we obtained good outcomes using arthroscopic inside-out medial meniscal repair combined with pie crusting for the release of the MCL, with or without ACLR. Level of Evidence: Level IV, therapeutic case series.